Harvesting of Microalgal Biomass - Xianhai Zeng; Xiaoyi Guo; Gaomin Su; Danquah, Michael; Xiao Dong Chen; Lu Lin; Yinghua Lu (2016)
Dewatering of microalgal broth is a key unit operation for producing algal fuels and other products. Dewatering is expensive and a factor hindering the commercialization of low-value algal products such as fuel oils. The extremely dilute nature of microalgae cultures coupled with the small size of the algal cells makes dewatering energy intensive. This chapter provides an overview of some of the key dewatering methods applicable to microalgal broths.